Editorial (2020)
As the editor of this Journal and former graduate student and professor for about 5 years, I want to applause to the 60th anniversary of the Program of Agronomic Engineering at the Universidad Pedagógica y Tecnológica de Colombia, Tunja campus, which is currently a publishing institution of this Journal